2017
DOI: 10.1016/j.heliyon.2017.e00458
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic toxicity assessment of cationic liposome exposure in healthy and chronic alcohol fed mice

Abstract: The utilisation of nanoparticles as the means of targeted delivery of therapeutics and/or imaging agents could greatly enhance the specific transport of biologically active payloads to target tissues while avoiding or reducing undesired side-effects. To allow for this to become a reality, the question of potential toxicological effects needs to be addressed. In the present investigation, a cationic liposome with prospective for medical applications was constructed and thoroughly assessed for any material-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…As a side note, it should be stated that the liposome-related data in this study fit very well with a previous investigation in which a comprehensive in vitro analysis found that potential adverse effects after exposure of endothelial cells and macrophages to liposomes did not induce a cytotoxic or inflammatory response in any of the experimental conditions [36]. In addition, the same liposomes were also shown to be highly biocompatible after intravenous exposure of C57BL/6 mice [42]. This is the first study of its kind in which liposome association by the three main leukocyte subpopulations in human blood is quantified.…”
Section: Discussionsupporting
confidence: 90%
“…As a side note, it should be stated that the liposome-related data in this study fit very well with a previous investigation in which a comprehensive in vitro analysis found that potential adverse effects after exposure of endothelial cells and macrophages to liposomes did not induce a cytotoxic or inflammatory response in any of the experimental conditions [36]. In addition, the same liposomes were also shown to be highly biocompatible after intravenous exposure of C57BL/6 mice [42]. This is the first study of its kind in which liposome association by the three main leukocyte subpopulations in human blood is quantified.…”
Section: Discussionsupporting
confidence: 90%
“…The surface charge of nanocarriers is another challenge to SDDS design, as the surface charge largely determines the interaction between the body and nanocarriers. Nanocarriers with positive charges, or cationic nanocarriers, show greater toxicity compared to ones with negative surface charges [214] , [288] . A shell around the nanocarriers plays a vital role in reducing the toxicity of nanocarriers.…”
Section: Toxicity Study Of Eight Nanocarriersmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] However, mainstream cationic transfection agents are associated with several drawbacks such as lipid-induced cytotoxicity and non-applicability in hard-to-transfect cells. [11][12][13][14][15][16][17][18] Among these hard-to-transfect cells, macrophages are notoriously difficult to transfect using liposomes and, therefore, are usually genetically manipulated using viral vectors; but, preparation of these viral vectors could be challenging and presents biosafety threats to researchers. 19 Macrophages are a type of immune cells specialized in engulfing hazardous biological entities, eg, dead cells, pathogens, cancer cells, bacteria etc.…”
Section: Introductionmentioning
confidence: 99%